Лірична проза Лесі Українки: питання жанрової ідентифікації - Левчук, Юлія; Levchuk, Yulіia (Східноєвропейський національний університет імені Лесі Українки, 2016)
Досліджено проблеми жанру в прозовій творчості Лесі Українки. Зроблено спробу диференціювати закономірності письма, які реалізовані в прозових текстах авторки. Зокрема, зосереджено увагу на так званій ліричній прозі, ос- новними принципами якої є суб’єктивність, медитативність, філософський зміст, екзистенційна тематика. The research concerns the problem of the genre in the prose works of Lesia Ukrainka. An attempt is made to differentiate the patterns of writers’ abilities implemented in prose texts of the author. In particular, attention is focused on the so-called lyrical prose, the basic principles of which are subjective, meditative, philosophical content, existential themes. For example, the existential problem of time, developed in the work “Late” (1893), allows you to define its genre as a philosophical sketch. Comparative analysis of the genre pairs that constitute the texts of Lesia Ukrainka “Error (Prisoner Thoughts)” (1905) and O. Kobylianska “The Soldier’ Letter Sentenced to Death for His Wife” (1916), led to the conclusion that the same the concept of “prisoner” the writers interpreted from different points of view, at what Lesіa Ukrainka distinguished by deep philosophical content. Also analyzed the texts of works “Blind” (1903) and “Ghost” (1905), a genre which is defined as a symbolist and expressionist sketches in accordance.
The Lyrical Prose of Lesia Ukrainka: the Question of Genre Identification.
Keywords: Леся Українка; проза; ліризм; філософський етюд; архетип; екзистенційність; Lesіa Ukrainka; prose; lyrical; philosophical sketch; archetype; existential